2021
DOI: 10.1021/acsphotonics.1c00707
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Advances in Quantum Dot Lasers and Integration with Si Photonic Integrated Circuits

Abstract: Epitaxially grown quantum dot (QD) lasers are emerging as an economical approach to obtain on-chip light sources. Thanks to the three-dimensional confinement of carriers, QDs show greatly improved tolerance to defects and promise other advantages such as low transparency current density, high temperature operation, isolator-free operation, and enhanced four-wave-mixing. These material properties distinguish them from traditional III–V/Si quantum wells (QWs) and have spawned intense interest to explore a full s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 83 publications
(143 reference statements)
0
41
0
Order By: Relevance
“…Changes in the strain conditions during the growth of QDs from sample to sample while increasing the In content in the buffer layer underneath may lead to inducing an in-plane asymmetry of QDs’ shape or strain anisotropy, both affecting the mixing of valence band states (where the light and heavy-hole states mixing is of crucial importance), leading to a non-zero DOLP of QD emission [ 59 ]. The possible QD shape asymmetry is characteristic for the QDs’ growth under lower strain, and hence the stronger influence of the atomic steps on growth anisotropy (along the crystallographic directions [110] and [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]) may occur, as it was already observed for other types of dots grown by MBE in conditions of smaller difference in the lattice constants between the substrate/buffer and the QD materials [ 54 , 55 ]. It is difficult to resolve which of the parameters (QD shape asymmetry or strain anisotropy) is the main factor responsible for the observed DOLP change, especially for inhomogeneous systems where the differences in dot-to-dot shape and strain variations can be significant and only average properties can be specified for an ensemble of QDs [ 59 , 60 , 61 ], but one can expect that both do contribute.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the strain conditions during the growth of QDs from sample to sample while increasing the In content in the buffer layer underneath may lead to inducing an in-plane asymmetry of QDs’ shape or strain anisotropy, both affecting the mixing of valence band states (where the light and heavy-hole states mixing is of crucial importance), leading to a non-zero DOLP of QD emission [ 59 ]. The possible QD shape asymmetry is characteristic for the QDs’ growth under lower strain, and hence the stronger influence of the atomic steps on growth anisotropy (along the crystallographic directions [110] and [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]) may occur, as it was already observed for other types of dots grown by MBE in conditions of smaller difference in the lattice constants between the substrate/buffer and the QD materials [ 54 , 55 ]. It is difficult to resolve which of the parameters (QD shape asymmetry or strain anisotropy) is the main factor responsible for the observed DOLP change, especially for inhomogeneous systems where the differences in dot-to-dot shape and strain variations can be significant and only average properties can be specified for an ensemble of QDs [ 59 , 60 , 61 ], but one can expect that both do contribute.…”
Section: Resultsmentioning
confidence: 99%
“…Semiconductor self-assembled epitaxial quantum dots (QDs) have been demonstrated to be suitable candidates for use in a wide range of optoelectronic devices, from lasers [ 1 , 2 ], optical amplifiers [ 1 , 3 ], or other broadband sources [ 4 , 5 ] to quantum computing and quantum information processing employing QD-based non-classical emitters [ 6 , 7 , 8 , 9 , 10 ]. In particular, the possibility of controlling the parameters of QDs via the materials choice, and the related band structure and strain engineering, makes them attractive for applications due to the possibility of obtaining compatibility with the existing silica-based optical fiber infrastructure and emission in the high-transmission spectral range of telecommunication windows, characterized by the lowest attenuation in the third telecom or minimum optical signal dispersion in the second telecom windows [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following this lead, quantum dot (QD) based devices exhibit unique features, compared to QWs that are highly sought in neuromorphic schemes. Enhanced temperature insensitivity, originating from the three-dimensional confinement of carriers in the nanostructure, can alleviate the need for power-hungry active cooling schemes in QD based neuromorphic schemes [17]. Furthermore, recent works, have demonstrated that active QD layers can be grown directly over silicon, providing high-quality lasers [17], thus avoiding complex hybrid integration processes [18].…”
Section: Introductionmentioning
confidence: 99%
“…These QDs show excellent purity [24] and indistinguisability [25]. Moreover, as these quantum emitters are based on III-V semiconductors, they can be integrated in photonic integrated circuits [26][27][28] and even in silicon substrates [29]. With these materials choice, we present in the following the optimum design parameters to extract from the sample 3.6 GHz single-photon rates in a narrow cone of NA = 0.17.…”
Section: Introductionmentioning
confidence: 99%